Pembuatan Direktori Rumah Tahfidz Quran se-Kota Padang - Afriami, Zelka; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The study of this research in about creating a directory of Tahfidz Quran house in Padang City. The purpose is to describe about creating a directory for Tahfidz Quran house in Padang City. This research has been done by a descriptive method by visiting directly to Tahfidz Quran house in Padang City to observe and do some interviews. After the data analyzed, the conclusion explains some steps of creating a directory Tahfidz Quran: (1) collecting the data; (2) making notes about previous data then typing it to microsoft word; (3) determining the subject; (4) doing classification, and; (5) creating the directory.Keywords: creating, directory, and Tahfidz Quran.